Survival Strategy of Family dalam Meraih Generasi Emas Perspektif QS Al-Nisa’ Ayat 9 - M. Ilham; Patma; Muh. Mukmin Passa (STID Raudlatul Iman Sumenep, 2026)
This study aims to identify and analyze the survival strategies of Muslim families in facing challenges in the era of globalization, specifically within the context of forming a